2015
DOI: 10.3892/etm.2015.2497
|View full text |Cite
|
Sign up to set email alerts
|

Effect of penehyclidine hydrochloride on heart rate variability in hysteroscopy

Abstract: In order to evaluate the effect of different doses of penehyclidine hydrochloride (penehyclidine) on heart rate (HR) and HR variability (HRV) in hysteroscopy, 180 patients (American Society of Anesthesiologists grade I-II) were randomized equally to three groups: 0.5 mg penehyclidine and intravenous anesthesia (group I), 1.0 mg penehyclidine and intravenous anesthesia (group II) and saddle anesthesia combined with intravenous anesthesia (control group). HR and HRV, including total power (TP), low-frequency pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The major benefit of PHC compared with other anticholinergic drugs is that it does not cause muscarinic 2 receptor-associated cardiovascular side effects ( 14 ). PHC stabilizes the heart rate without autonomic nervous modulation ( 15 ). Our previous study demonstrated that PHC pre-treatment reduces myocardial apoptosis in rat hearts in vivo ( 16 ); however, its mechanism of action remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The major benefit of PHC compared with other anticholinergic drugs is that it does not cause muscarinic 2 receptor-associated cardiovascular side effects ( 14 ). PHC stabilizes the heart rate without autonomic nervous modulation ( 15 ). Our previous study demonstrated that PHC pre-treatment reduces myocardial apoptosis in rat hearts in vivo ( 16 ); however, its mechanism of action remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…PHC at a dose of 1.0 mg may be superior to 0.5 mg PHC in maintaining a stable heart rate, and reduces the incidence of bradycardia; however, the higher dose is less effective at maintaining sympathetic and parasympathetic balance. 13 Additionally, a study by Wang et al demonstrated that PHC reduced the incidence of intraoperative awareness in patients undergoing breast cancer surgery during general anesthesia. 14 …”
Section: Resultsmentioning
confidence: 99%